Marfan’s syndrome with rhegmatogenous retinal detachment: a case report and literature review - Subedi, Kumudini; Dulal, Prachi; Pradhan, Sangita; Byanju, Raghunandan (Journal of National Heart and Lung Society Nepal, 2023)
Background: Marfan’s syndrome is known to be a rare, multisystem disorder of connective tissue typically affecting cardiac, skeletal and ocular system. The only definitive diagnosis is by gene testing for autosomal dominant mutation of FBN1 gene encoding the regulation of fibrillin 1 located on chromosome 15q.3. Ocular manifestations appear early in life with most of the abnormalities being sight threatening. These incude ectopia lentis, high myopia, rhegmatogenous retinal detachment , open angle glaucoma etc. Ophthalmological examination plays vital role in early diagnosis and visual preservation. Case report: A 16 year old male presented with chief complaints of curtain like shadow in temporal visual field with present glasses for past 7 days. He had bilateral ectopia lentis with rhegmatogenous retinal detachment sparing the macula in the left eye. General examination of patient revealed physical features suggestive of Marfan’s syndrome. Although genetic testing was not possible, all features were suggestive of Marfan’s syndrome according to revised Ghent criteria. Pars plana vitrectomy with lens extraction with silicone oil injection was the treatment of choice. After an eventful post-operative period with silicone oil induced rise in intraocular pressure and 360 degrees peripheral anterior synechiae, early removal of silicone oil led to a good final visual outcome. Thus, with early detection and prompt treatment we were able to restore his visual quality of life. Conclusion: Although serious and vision threatening manifestations may occur in the eye in cases of Marfan’s syndrome, early diagnosis and prompt treatment may be able to salvage vision. It is necessary to keep patients on regular follow up and inform them of possible vision threatening ocular manifestations in the eye for early diagnosis and prompt management.